A novel method for the manufacture of porous structures with multi-component, coated pores - Siddiq, Abdur R.; Kennedy, Andrew R. (Elsevier, 2017)
A novel process is demonstrated which is able to produce porous structures with internal coatings. This is achieved using sacrificial porogens which are coated with a powder and which are then infiltrated by compression moulding using a molten polymer. The coating powder is transferred to the pore and multi-material or compositionally-gradient coatings are produced. The interconnectivity of the porous structure is reduced when the pores are coated, but can be increased by reducing the degree of powder coverage of the porogen.